Pemetaan Penggunaan Lahan Berbasis Citra Foto UAV (Unmanned Aerial Vehicle) Di Kelurahan Penarukan Kabupaten Buleleng - Astawa, Made; I Gede Yudiwisnawa; I Wayan Treman (Jurnal ENMAP (Environment and Mapping), 2024)
The increase in the number of people from year to year will certainly increase the need for land which currently, land conversion has been rampant from agricultural land to built land. Looking at the situstion that occurred in Penarukan Village, Buleleng Regency, where several agricultural lands have been converted into land for development. Therefore, mapping the use of moors, rice fields plantations and settlements is very necessary to interpret land use from UAV photos which aims to obtain up to date data that includes the distribution and area of land use. This research will use a visual interpretation elements which will be done manually, namely through on-screen digitization in ArcGIS software, Ground Check, and Interpretation Accuracy Test The results obtained from this study are the visualization of the distribution of land use from moorland by showing the distribution pattern randomly while the plantation visualization of the distribution pattern was spread evenly, and from residential land which followed the pattern of secondary transportation road, collectors and arteries while the visualization of the distribution of rice field land use where this rice field land is the most dominant land use others, with a total percentage of 45.38% with the visualization of the distribution pattern scattered randomly. The results of the classification of land use classes obtained 21 classes of land use which include Irrigation fields, Residential Houses, Mixed Gadens, Temples, Hotels, Sports Facilities, Educational Facilities, Fuel Pump Stations, Mosques, Bank Offices, Gardens, Housing, Tegalan, Stations/Terminals, Traditional Trade Centers and Health Centers. The area of the entire land use class of Penarukan village is 373.04 Ha. The accuracy level of the percentage of interpretation test results obtained is 100% based on verification of the 30 sampel points used.